Three levels model for differentiated pharmacist clinical activities in the Community Pharmacy – The practical application - Condinho, Monica (2015)
Introduction: In order to contribute for the real implementation of cognitive pharmaceutical services in Portugal, a three levels model of pharmacist clinical intervention in the community pharmacy, based on the differentiated patient´s health needs, was proposed by the authors [Three levels model for differentiated pharmacist clinical activities in the Community Pharmacy - The proposal. Accompanying paper]. Objective: To test the practical application of the proposed three levels model for differentiated pharmacist clinical activities in the community pharmacy. Methods: The three levels model was implemented in several community pharmacies. The philosophy of the model, to change the focus of community pharmacies from the product to the patient, was introduced under the supervision of a specialized pharmacist, responsible for the pharmacotherapeutic follow-up program. All the pharmacy professionals were instructed to ask the customer about the control of his health problem, whenever applicable. When no non-controlled health problem was detected, dispensing the product fulfils the costumer needs and is considered the level 1 service. If a non-controlled health problem was detected, the pharmacist considers the clinical situation and delivers the appropriate counselling, either immediately or delayed for a pharmaceutical consultation, configuring the level 2 service. When, at level 2, emerges the perception that simple and immediate actions would not control the health problem, the patient was invited to integrate the pharmacotherapeutic follow-up program, corresponding to the level 3 service. Results: The implementation of pharmacotherapeutic follow-up consultations (level 3) started in 2008 and paved the way for the development of this model. Until September 2013, one specialized pharmacist followed 430 patients with recurrent non-controlled health problems, performing around 3200 pharmaceutical consultations in 20 community pharmacies. The results available for one pharmacy (46 patients) show mean reductions of 26.4±7.68 mg/dL on total cholesterol (n=28; p=2.510x10-3), 1.9±0.73 % on glycated haemoglobin (n=29; p=0.022) and 26.2±3.79 mmHg on systolic blood pressure (n=23; p=6.197x10-7). Level 2 consultations started in May 2012. During the first 16 months of implementation in 5 pharmacies, 346 patients were enrolled. A total of 371 consultations were performed and mean reductions of 53.3±9.27 mg/dL in total cholesterol (n= 19; p=1.913x10-5), 18.3±2.26 mmHg in systolic blood pressure (n=42; p=4.657x10-10) and 0.2% in glycated haemoglobin (n=2) have been registered. Conclusion: The three levels model for differentiated pharmacist intervention, based on the pharmacy customer´s health needs, seem to be a suitable model for the routine implementation of cognitive pharmaceutical services in Portuguese community pharmacies. Based on this model, the pharmacy can answer to all their customer´s health needs and contributes for significant improvements on patient´s health condition.